2004
DOI: 10.1016/j.jaci.2004.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhaled corticosteroids on symptom severity and sputum mediator levels in chronic persistent cough

Abstract: Cough severity and sputum ECP levels are modestly reduced by inhaled corticosteroids in patients with chronic cough persisting for more than 1 year. LTB(4), Cys-LT, PGE(2), IL-8, myeloperoxidase, and TNF-alpha levels are unaltered by this therapy. This raises the possibility that drugs targeted to reduce the effects of these mediators might be of benefit in chronic persistent cough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 45 publications
3
56
0
3
Order By: Relevance
“…Tussive inflammatory mediators, which may activate afferent sensory nerve endings, have been implicated in the pathogenesis of cough [7,38,39]. Inhalation studies in healthy individuals [9,10] and inhibition studies of the specific antagonists of inflammatory mediators in asthmatic patients [11] have shown that prostanoids such as PGE 2 , PGF 2 α and TXA 2 are associated with the cough reflex.…”
Section: Discussionmentioning
confidence: 99%
“…Tussive inflammatory mediators, which may activate afferent sensory nerve endings, have been implicated in the pathogenesis of cough [7,38,39]. Inhalation studies in healthy individuals [9,10] and inhibition studies of the specific antagonists of inflammatory mediators in asthmatic patients [11] have shown that prostanoids such as PGE 2 , PGF 2 α and TXA 2 are associated with the cough reflex.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, placebo-controlled 2-week trial of inhaled FP (500 mg twice a day) in patients with normal spirometry and cough for more than 1 year, significant improvement in cough symptoms and in the levels of airway inflammatory mediators was observed (Chaudhuri et al, 2004). However, a randomized, placebo-controlled crossover study of lower dose ICS (200 mg of BDP twice daily) given for a shorter period of time (2 weeks) did not appear to be effective (Evald et al, 1989).…”
Section: Glucocorticosteroidsmentioning
confidence: 99%
“…Histamin, prostoglandin E 2 ve substance P, bradikinin artışı da öksürük refleksini aktive eder. Bu durum ACE inhibitörlerinin kullanımına bağlı kronik öksürük hastaların yanı sıra idiyopatik öksürük olgularında da ortaya konulmuştur [48][49][50].…”
Section: öKsürük Refleksi Aşırı Duyarlılığıunclassified